2018
DOI: 10.1038/s12276-018-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA DANCR promotes colorectal cancer proliferation and metastasis via miR-577 sponging

Abstract: Long non-coding RNAs (lncRNAs) play key roles in various malignant tumors, including colorectal cancer (CRC). Long non-coding RNA differentiation antagonizing non-protein coding RNA (DANCR) is overexpressed in CRC patients, but whether it affects CRC proliferation and metastasis via regulation of heat shock protein 27 (HSP27) remains unclear. In the present study, we found that DANCR was highly expressed and correlated with proliferation and metastasis in CRC. In addition, we demonstrated that DANCR and HSP27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 50 publications
8
88
0
Order By: Relevance
“…One critical mechanism by which lncRNAs regulate gene expression is acting as ceRNAs to sponge targeted miRNAs (Salmena et al, 2011). This is also true for DANCR, not only because several miRNAs have been identified as direct targets of DANCR, but also the function of DANCR is prominently mediated through downregulating the expression of these miRNAs, as reported by recent studies Lu et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Xu et al, 2018;Yang et al, 2018), to name a few. Combining predictive methods and some biochemical experiments, we demonstrate that miR-874-3P is a new binding target of DANCR and that by suppressing the inhibitory effect of miR-874-3P on ATG16L1 expression via interacting and decreasing miR-874-3P level, DANCR possesses an ability to upregulate ATG16L1 expression.…”
Section: Disscussionmentioning
confidence: 89%
“…One critical mechanism by which lncRNAs regulate gene expression is acting as ceRNAs to sponge targeted miRNAs (Salmena et al, 2011). This is also true for DANCR, not only because several miRNAs have been identified as direct targets of DANCR, but also the function of DANCR is prominently mediated through downregulating the expression of these miRNAs, as reported by recent studies Lu et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Xu et al, 2018;Yang et al, 2018), to name a few. Combining predictive methods and some biochemical experiments, we demonstrate that miR-874-3P is a new binding target of DANCR and that by suppressing the inhibitory effect of miR-874-3P on ATG16L1 expression via interacting and decreasing miR-874-3P level, DANCR possesses an ability to upregulate ATG16L1 expression.…”
Section: Disscussionmentioning
confidence: 89%
“…55,56 DANCR could upregulate colon cancer cell proliferation and migration ability by sponging MIR577 and increase the expression of HSPB1. 56 Huang et al and Zhang et al concluded that SNHG15 and SNHG16 were both highly expressed in colon cancer samples. [57][58][59] SNHG15 could only increase the protein level of SNAI2 but not the mRNA level through preventing SNAI2's ubiquitin.…”
Section: Snhgs In Colorectal Cancermentioning
confidence: 96%
“…It was determined as an individual poor prognosis factor in colon cancer . DANCR could upregulate colon cancer cell proliferation and migration ability by sponging MIR577 and increase the expression of HSPB1 . Huang et al and Zhang et al concluded that SNHG15 and SNHG16 were both highly expressed in colon cancer samples .…”
Section: Biological Functions and Mechanisms Of Snhgs In Digestive Camentioning
confidence: 99%
“…Mechanistically, lncRNA acts as a ceRNA to sponge target miRNA response elements and imposing its post‐transcriptional regulatory level. For instance, DANCR is highly expressed in late stage of cancers and is correlated with advanced cancer progression and poor OS of colorectal cancer . LncRNA UCA1 promotes the chemical drug resistance of bladder carcinoma through modulating Wnt signaling pathway .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, DANCR is highly expressed in late stage of cancers and is correlated with advanced cancer progression and poor OS of colorectal cancer. 7 LncRNA UCA1 promotes the chemical drug resistance of bladder carcinoma through modulating Wnt signaling pathway. 8 Additionally, Linc00152 is involved in cell apoptosis, cell cycle arrest, epithelial-mesenchymal transition (EMT), as well as cell invasion and migration of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%